Questioning the Phenomenological Foundations of Marton’s Research Approach - Moroz, Jacek (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The purpose of this article is to try to answer the question: is phenomenographic research underlying (in a broad sense) phenomenological assumptions? It is an important question because opinions on this topic are divided. Some researchers argue that phenomenography derive from philosophical phenomenology. Phenomenology is even treated as a philosophical foundation of phenomenographic research. In this article I argue that the statement on similarities and connections between the two approaches and especially the claim that phenomenography has phenomenological roots are based on mistaken interpretation of the method created by Ference Marton.